2017
DOI: 10.4028/www.scientific.net/kem.742.753
|View full text |Cite
|
Sign up to set email alerts
|

Light Weight Vehicle in Natural Fibre Composite

Abstract: Combined with shared service points in prime locations the use of Light Electric Vehicles (LEV) can help optimize the cost expensive „last mile“ of parcel service. [1] At the same time, a shared service point enables the switch from diesel driven engines to muscle-powered electric driving in cities. It is known, that in city operating courier services up to 80 % of actual used diesel fuel can be substituted by muscle supported electric driving. [2] To cover the needs of global operating parcel services a muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Besides being economical and easily available, natural fibers also exhibit various attractive characteristics, such as low density, good insulation, thermal properties, high specific strength, and minimal energy consumption during processing . PALF has received more attention as reinforcing material compared with other natural fibers, such as jute, hemp, kenaf, and flax . Pineapple leaves are an agricultural waste material, used to produce fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being economical and easily available, natural fibers also exhibit various attractive characteristics, such as low density, good insulation, thermal properties, high specific strength, and minimal energy consumption during processing . PALF has received more attention as reinforcing material compared with other natural fibers, such as jute, hemp, kenaf, and flax . Pineapple leaves are an agricultural waste material, used to produce fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Two construction methods, mixed steel/GFRP and GFRP and the elaboration of the ergonomics of the driver (Figure 1a-c) were developed using CATIA V5 6R2020 software. For weight optimisation and fibre composite design, finite element models were used with ANSYS AIM 16.2 software and the Workbench PlugIn LS-PrePost ® V4.7.7 [13]. Material parameters required for the component design were determined using the relevant material testing standards or taken from material data sheets, when available.…”
Section: Methodsmentioning
confidence: 99%
“…proposed a comparison for the development of a light‐weight e‐vehicle with a sandwich structure made from natural fibre composite decking laces on a polyester (PET) foam core. They studied the weight savings on the Cargo Cruiser and proposed a 2 nd generation vehicle based on their studies [217] . Fantuzzi et al.…”
Section: Sustainable Biopolymers In Automobilesmentioning
confidence: 99%
“…They studied the weight savings on the Cargo Cruiser and proposed a 2 nd generation vehicle based on their studies. [217] Fantuzzi et al reported the material characterization for woven biocomposites based on flax fibres and studied them as an alternative to carbon/glass reinforced components such as front and rear bumpers in structural automotive applications. The mechanical behaviour of micro e-vehicles was tested using finite element modelling by altering the fibre reinforced materials.…”
Section: Natural Fibresmentioning
confidence: 99%